Production functions for 14 subsectors of Irish industry, 1960-1968, for purpose of estimating employment - Henry, EW (Economic & Social Studies, 1972)
During this past year two important research publications on production functions for Irish industry have appeared, by Kennedy and by Farley. The first analyses the growth rate of net output per unit of labour as a function of the growth rate of net output, and the growth rate of employment also as a function of the growth rate of net output, for manufacturing and its subsectors. The second estimates growth rate of net output per man-year as a function of three variables: the rate of increase of the capital/labour ratio, the importance of capital in the production process, and the rate of technical change, for sub-sectors of manufacturing.
Keywords: Irish Industry; Employment